2004
DOI: 10.1002/cncr.20489
|View full text |Cite
|
Sign up to set email alerts
|

Adult de novo acute myeloid leukemia with t(6;11)(q27;q23)

Abstract: BACKGROUND Acute myeloid leukemia (AML) with t(6;11)(q27;q23) is a well established but rare entity, and few studies have reported the full clinical, hematologic, and outcome data of patients with this disease. METHODS To characterize the features of t(6;11) AML, the authors searched the Cancer and Leukemia Group B (CALGB) cytogenetic database comprising 2667 adults with newly diagnosed, de novo AML and identified 16 patients (0.6%) with t(6;11). A review of the literature identified 33 adults with de novo t(6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 34 publications
(35 reference statements)
0
10
0
1
Order By: Relevance
“…Interestingly, both of these abnormalities have been associated with a poor prognosis in previous studies, [43][44][45][46][47] including a recent large international pediatric study considering 756 cases of AML with MLL translocations. 47 In the latter study, the most favorable outcome was observed in cases with t(1;11)(q21;q23), although this abnormality was too infrequent in our series (n ϭ 3) to consider its prognostic significance in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both of these abnormalities have been associated with a poor prognosis in previous studies, [43][44][45][46][47] including a recent large international pediatric study considering 756 cases of AML with MLL translocations. 47 In the latter study, the most favorable outcome was observed in cases with t(1;11)(q21;q23), although this abnormality was too infrequent in our series (n ϭ 3) to consider its prognostic significance in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In adult AML, the poor outcome of patients with a t(6;11)(q27;q23) has been reported before, and adults with this specific translocation do equally bad (2-year OS, 13%). 29 Of interest, children with a t(6;11)(q27;q23) have a higher WBC and older age at presentation than other MLL-rearranged cases. We could not prove that allogeneic HSCT was of benefit in these patients, but numbers were limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, t(6;11) was shown to be an independent poor prognostic feature in adult AML (Tables 2). Adverse outcomes of patients with t(6;11) have been reported in pediatric AML 12 and adult AML by Cancer and Leukemia Group B 15 and the German AML Intergroup. 16 Given the dismal outcomes of these patients, clinical trials using novel strategies should be encouraged for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, information on the potential therapeutic role of allogeneic stem cell transplantation (allo-SCT) in this subgroup is scarce, as most of the published studies involved groups that were too small to allow definitive conclusions. 15, 16 …”
Section: Introductionmentioning
confidence: 99%